History of Western Philosophy - Tubbs, N. author. aut Link
X, 190 p.
Keywords: Nigel Tubbs takes the history of Western philosophy to be the search for first principles. Arguing that neo-Platonic logic, fundamentally misunderstanding the negative, posited philosophical thought as error. Kant and Hegel later re-educated the modern mind about negation in logic, transforming the way modern philosophy contests first principles.